2005
DOI: 10.1021/bi047342s
|View full text |Cite
|
Sign up to set email alerts
|

Green Fluorescent Protein-ExpressingEscherichia colias a Selective Probe for HOCl Generation within Neutrophils

Abstract: Escherichia coli were transformed by electroporation to introduce a plasmid harboring a GFP gene-containing vector. The fluorescence of the purified GFP isolated from the transformant was quenched by myeloperoxidase (MPO)-generated HOCl, by peroxynitrous acid (ONOOH) and by enzymatically or radiolytically generated NO(2)(.) but not by other putative neutrophil-generated oxidants. Fluorescence from the bacterium was effectively quenched by HOCl but not peroxynitrite, oxidizing radicals derived from its O-O bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 63 publications
4
45
2
Order By: Relevance
“…2, A and B). Moreover, these concentrations have been estimated previously to exist within neutrophil phagosomes (31,(33)(34)(35)(36)(37); albeit, recent studies indicate the steady-state concentration of H 2 O 2 is much lower (38). As with the concentration-dependent killing of S. aureus by either H 2 O 2 or HOCl, there was limited time-dependent effect on viability (i.e., Ͻ100% survival) of MW2 following exposure to these microbicides (Fig.…”
Section: S Aureus Is Resistant To Major Neutrophil Microbicidesmentioning
confidence: 79%
“…2, A and B). Moreover, these concentrations have been estimated previously to exist within neutrophil phagosomes (31,(33)(34)(35)(36)(37); albeit, recent studies indicate the steady-state concentration of H 2 O 2 is much lower (38). As with the concentration-dependent killing of S. aureus by either H 2 O 2 or HOCl, there was limited time-dependent effect on viability (i.e., Ͻ100% survival) of MW2 following exposure to these microbicides (Fig.…”
Section: S Aureus Is Resistant To Major Neutrophil Microbicidesmentioning
confidence: 79%
“…Furthermore, as noted above, Mayer and coworkers have reported widespread tyrosyl nitration within LPS/IFγ-activated RAW cells within roughly the same time scale (26); although in this case the target sites were not identified, they must have involved other intracellular proteins. These data suggest that, like all other heme peroxidases that have been investigated (38,70), COX-2 can oxidize available NO 2 -at its peroxidase site (71) via peroxide-generated compounds I and II to NO 2 · , which is then diffusible from the active site. We recently found that NO 2 · is remarkably toxic to Escherichia coli, with an LD 50 comparable to that of the much more strongly oxidizing and potently microbicidal CO 3 ·-radical anion (28), and Klebanoff has demonstrated that E. coli are also effectively killed when exposed to a cell-free MPO-H 2 O 2 -NO 2 -system (70).…”
Section: Physiological Implicationsmentioning
confidence: 79%
“…PMN phagocytosed bacteria are usually killed rapidly (14,18), and we therefore set out to investigate the fate of phagocytosed Ag43-expressing bacteria. Accordingly, the survival rate of such bacteria was monitored for 120 min (Fig.…”
Section: Resultsmentioning
confidence: 99%